Inserción laboral de las personas afroecuatorianas en las Empresas e Instituciones Públicas del cantón Quevedo, provincia de Los Ríos, año 2014 - Monroy Pérez, María Fernanda (2016)
This research is a detailed study allows to know important information about the relationship between employment discrimination and racism in companies and public institutions in Quevedo canton Los Ríos province, the employment of Afro-Ecuadorians is diagnosed by determining the factors that influence the employment of Afro-Ecuadorian race, Also the quality of life and socio-economic position of the race is set, Invoking criteria authors whose specialized knowledge was a great contribution to develop research results. The research was applied documentary or bibliographic review which allowed for, detection, obtaining, query, extraction, and collection, through the specification refers to the preparatory stage of work, field which is applied by means of evaluation techniques and instruments to collect information on the Afro-Ecuadorian people in Quevedo canton, methodological part was supported by data that allowed determining the variables in studies. The observation method is based on the information through direct verifications administrative staff of enterprises and public institutions in Quevedo Canton. Through deductive method of situational analysis it was performed with the inductive method was determined concepts, laws, principles defined by different authors which was applied both in defining the problem and the solution, surveys were used as a verification tool a survey questionnaire, the results support the evaluation. At the end of this investigation it was determined, there is very little participation in administrative charges by afroecuatorianos, which is a clear manifestation of racism and thus reflects one of the causes that determine access to economic resources, education, and services, providing the Ecuadorian state. Keywords.Insertion, discrimination, racism, inclusion